THE FIVE KARTIKA VALUES: DEVELOPING STUDENT CHARACTER IN ISLAMIC RELIGIOUS EDUCATION - Ana Rosanti; Roihatun Zakkiyah; Roshyana Herawati; Santika Dewi Anggraeni; Erna Labudasari; Aliet Noorhayati Sutrisno (STKIP Citra Bakti, 2026)
This study aims to examine the role of Kartika values in developing the character of students in SD Kartika XIX-6. This research is motivated by the fact that there are still problems of student character such as lack of discipline and responsibility, so efforts are needed to strengthen and develop character values in a sustainable manner in the school environment. This study uses a qualitative method with a descriptive approach, the subjects in this study consist of 23 students in grade III as questionnaire respondents, and teachers as research informants. The data collection method was carried out through observation, interviews, and questionnaires with instruments in the form of observation sheets, interview guidelines, and questionnaire sheets. The results of the study show that the Kartika values have been applied through habituation activities, classroom learning, and school programs. The application has an impact on the formation of disciplined behavior, responsibility, and active involvement of students in learning activities and school activities, in addition, students have begun to show attitudes that reflect virtuous values, love for the homeland, intelligent, skilled and disciplined in daily life in the school environment.